La tutela dell’identità delle minoranze religiose deve potersi avvalere di “un giudice e un giudizio” (ancora sulla sentenza della Corte costituzionale n. 52 del 2016) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1- La qualificazione giuridica è attribuzione costituzionale esclusiva del potere giudiziario - 2. La qualificazione giuridica delle confessioni religiose … - 3. (segue) e il loro diritto all’identità - 4. L’espediente del “doppio binario” - 5. L’insopprimibile garanzia della tutela giurisdizionale dei diritti è (ancora) principio supremo dell’ordinamento costituzionale - 6. Il petitum del ricorso per conflitto di attribuzioni tra poteri dello Stato, e l’obbligo di attenersi al thema decidendum - 7. I poteri del Governo nell’esame dell’istanza di accesso all’intesa - 8. Le improvvide conseguenze dell’avere ritenuto il diniego governativo “atto politico”: dal “pluralismo aperto” al “pluralismo discrezionalmente regolamentato”.For the protection of their identity, religious minorities should have “a judge and a judgment” at their disposal (again on the judgment of the Constitutional Court no. 52 of 2016)ABSTRACT: The article links the theme of the legal qualification of an association that calls itself a “religious confession” in order to have relationships with the State, according to the provisions laid down in the third paragraph of art. 8 of the Constitution, with the theme of the right of religious minorities to have an identity. It intends to prove that the document that the government issues in order to deny such a qualification is not a “political action” exempt from the control of the judicial authority, contrary to ruling no. 52 of 2016 of the Constitutional Court. The identity of religious minorities is protected by the guarantees offered by art. 24 of the Constitution, from which the Constitutional Court draws the supreme principle of jurisdictional protection of rights, the foundation of any democratic system, that guarantees to all, for any dispute, “a judge and a judgment”.